UJI EFEKTIVITAS KONSENTRASI ZAT PENGATUR TUMBUH TERHADAP PERTUMBUHAN BIBIT RAMIN (Gonystylus bancanus) DENGAN FREKUENSI PMBERIAN BERBEDA - Normalida Amalia; Emmy Winarni; Gusti Syeransyah Rudy (Universitas Lambung Mangkurat, 2020)
The aims of this research was to compare the respon of ramin seedlings growth by giving the different Plant Growth Regulator (PGR) concentrations and frequencies. Benefits of this research is to give information on ramin seedlings growth response to the provision of PGR on the growth of ramin seedlings useful in the development of sylvicultural technique for ramin hatchery to expedite the growth. This Research using experimental method by the difference concentration of Plant Growth Regulator (PGR), 0 % , 5% and 10 %, the frequencies of aplications were every 3 and 7 days. Data was analyzed using factorials randomized completely design (CRD). The results of this research showed the best of additional leaves and height of seedlings with the greatest value was in concentration of PGR 5% and the frequency of aplication every 3 days, with each everages 1.11 leaves and 0.77 cm. Keywords: Ramin Seedlings, Plant Growth Regulator